Degradation of 1,2,4-Trichloro- and 1,2,4,5-Tetrachlorobenzene by Pseudomonas Strains - Sander, Peter (1991)
Two Pseudomonas sp. strains, capable of growth on chlorinated benzenes as the sole source of carbon and energy, were isolated by selective enrichment from soil samples of an industrial waste deposit. Strain PS12 grew on monochlorobenzene, all three isomeric dichlorobenzenes, and 1,2,4-trichlorobenzene (1,2,4-TCB). Strain PS14 additionally used 1,2,4,5-tetrachlorobenzene (1,2,4,5-TeCB). During growth on these compounds both strains released stoichiometric amounts of chloride ions. The first steps of the catabolism of 1,2,4-TCB and 1,2,4,5-TeCB proceeded via dioxygenation of the aromatic nuclei and furnished 3,4,6-trichlorocatechol. The intermediary cis-3,4,6-trichloro-1,2-dihydroxycyclohexa-3,5-diene (TCB dihydrodiol) formed from 1,2,4-TCB was rearomatized by an NAD(+)-dependent dihydrodiol dehydrogenase activity, while in the case of 1,2,4,5-TeCB oxidation the catechol was obviously produced by spontaneous elimination of hydrogen chloride from the initially formed 1,3,4,6-tetrachloro-1,2-dihydroxycyclohexa-3,5-diene. Subsequent ortho cleavage was catalyzed by a type II catechol 1,2-dioxygenase producing the corresponding 2,3,5-trichloromuconate which was channeled into the tricarboxylic acid pathway via an ordinary degradation sequence, which in the present case included 2-chloro-3-oxoadipate. From the structure-related compound 2,4,5-trichloronitrobenzene the nitro group was released as nitrite, leaving the above metabolite as 3,4,6-trichlorocatechol. Enzyme activities for the oxidation of chlorobenzenes and halogenated metabolites were induced by both strains during growth on these haloaromatics and, to a considerable extent, during growth of strain PS12 on acetate.